2016
DOI: 10.1182/blood-2015-09-669317
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty 2: a novel attenuator of B-cell receptor and MAPK-Erk signaling in CLL

Abstract: Key Points• SPRY2 is downregulated in CLL cells from patients with poor prognosis. • SPRY2 is negative regulator of Syk-mediated BCR and MAPK-Erk signaling in CLL.Clinical heterogeneity is a major barrier to effective treatment of chronic lymphocytic leukemia (CLL). Emerging evidence suggests that constitutive activation of various signaling pathways like mitogen-activated protein kinase-extracellular signal-regulated kinase (MAPK-Erk) signaling plays a role in the heterogeneous clinical outcome of CLL patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…In this study, we found SPRY2 regulated the expression of c-RAF, p-MEK, and p-ERK in HCC, but had no effect on k-RAS, MEK and ERK. Therefore, SPRY2 might exert its ERK inhibitor role via suppressing c-RAF in HCC, which were consistent with prior studies in leukemia 38 , 39 . RAF-MAPK/ERK was an important signaling for targeting drugs such as regorafenib and sorafenib, thus our findings potentially provided a new clue for developing anovel therapeutic approach for HCC 40 .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found SPRY2 regulated the expression of c-RAF, p-MEK, and p-ERK in HCC, but had no effect on k-RAS, MEK and ERK. Therefore, SPRY2 might exert its ERK inhibitor role via suppressing c-RAF in HCC, which were consistent with prior studies in leukemia 38 , 39 . RAF-MAPK/ERK was an important signaling for targeting drugs such as regorafenib and sorafenib, thus our findings potentially provided a new clue for developing anovel therapeutic approach for HCC 40 .…”
Section: Discussionsupporting
confidence: 91%
“…An informed written consent was obtained from each participant. The cells were isolated as previously described [36]. …”
Section: Methodsmentioning
confidence: 99%
“…In B‐cell lymphoma, Sprouty2 is epigenetically silenced and promotes cell proliferation . Sprouty2 is also downregulated in chronic lymphocytic leukemia and is an important negative regulator of B‐cell receptor‐mediated ERK activation . In multiple myeloma, Sprouty2 is downregulated by miR‐21 expression .…”
Section: Roles Of Sprouty/spred During Tumorigenesis and Metastasismentioning
confidence: 99%
“…2 Sprouty2 is also downregulated in chronic lymphocytic leukemia and is an important negative regulator of B-cell receptor-mediated ERK activation. 52 In multiple myeloma, Sprouty2 is downregulated by miR-21 expression. 15,86 High expression of Sprouty4 is associated with a favorable prognosis in patients with AML.…”
Section: Sprouty/spred and Hematological Malignanciesmentioning
confidence: 99%